Perancangan Interior Gemstone Gallery di Surabaya - Jessica Angelia Purna Wijaya; Sriti Mayang Sari; Jean Francois Poilot (Intra, 2016)
Jewelery is one of things for making the looks better. One of the most populer jewelery is gemstone, but not every people understand which the gemstone that has an original quality or not. So that, Gemstone Gallery is designed as the gemstone jewelery centre in Surabaya. This place is provide demands of gemstone with support service, consider the high market place that become tight and enscure. Gemstone Gallery at Surabaya makes people have a way easier for searching and guiding all things about gemstone, such as information and gallery, the transaction of gemstone, consultation, and the other facilities.